The relationship between job satisfaction and social skill / Ellail Ain Mohd Aznan ... [et al.] - Mohd Aznan, Ellail Ain; Mohd Kassim, Ahmad Fikri; Othman, Nuraimi; Md Yusuf, Mohd Khairulanwar; Amir, Nurul Hidayah (Universiti Teknologi MARA, Perlis, 2019)
Emotional Intelligence (EI) which can be defined as emotion regulations dimension becomes an essential element needed by an employee in achieving the organizational goals. It is also found that there is a strong relationship between emotional intelligence and job satisfaction. Job satisfaction is one of the elements which had been eagerly discussed, however there is a limited number in study focusing on the relationship between job satisfaction and the dimension in emotional intelligence which is social skill. This study is focusing on the sport organization employees, 148 respondents had giving their cooperation by answering the developed questionnaire. The findings show that, social skill had a positive and significant relationship with job satisfaction. With p<0.005, this shows that there is a significant relationship not to be forgotten the value of correlation is .857 which classified as high level of correlation. This shows that social skill will positively affects the job satisfaction for employees in sport organization.